Switched control to human-robot bilateral interaction for guiding people - Leica Arteaga, Paulo Cesar (2014)
This paper presents a switched control strategy to interprete and design a human-robot bilateral interaction when a human follows a non-holonomic mobile robot at a desired distance while the robot is already following a known path. Furthermore, it proposes and experimentally validates a model that mathematically describes the human behavior when performing the specific task of tracking a mobile robot. This model is useful for the purposes of the control system design and its associated stability analysis. A switched system is proposed to model the complete human-robot behavior. The switching strategy is based on the human-robot relative position and on the human intention to follow the robot. Control errors are defined in terms of human to robot and robot to path instantaneous distances. Stability analysis for the individual controllers, as well as for the complete switching system, are provided by considering Lyapunov theory. Real human-robot interaction experiments show the good performance of the proposed control strategy.